Pelatihan Pembuatan LKPD dan Video Pembelajaran dengan Pendekatan CRT melalui Aplikasi Canva bagi Guru Sekolah Dasar: Professional Development Workshop on Creating Student Worksheets and Educational Videos Using a Culturally Responsive Teaching Approach with Canva for Elementary School Teachers - Rusnilawati, Rusnilawati; Rahmawati, Ratih Oktavia; Amalia, Renata Rizky; Kurniasih, Reni; Aguvia, Rifani Dwi; Pamungkas, Romario Seger Aji; Ronalia, Ronalia; Nisa’, Rosyidatun; Pratiwi, Sabilla; Mardiana, Sela; Hazima, Atika Azzahro; Rahman, Farizky (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The COVID-19 pandemic has accelerated the need to enhance learning in the digital era, focusing on developing students' critical thinking, innovation, and creativity through technology-based education. This training addresses several key issues: (1) many teachers at Penggok 3 State Elementary School in Sragen struggle with using digital technology to support learning; (2) the Culturally Responsive Teaching (CRT) approach is rarely applied; (3) students' interest in Indonesian culture is low; and (4) integrating technology into education is now essential. Teacher training is crucial for developing individual capabilities to create a better learning environment. This training aims to enhance primary school teachers' understanding and application of CRT, enabling them to design student worksheets (Lembar Kerja Peserta Didik - LKPD) and educational videos that reflect students' cultural diversity. Additionally, it aims to develop teachers' skills in using the Canva graphic design platform to create engaging, interactive, and culturally relevant LKPD and educational videos. The training on creating LKPD and educational videos with a CRT approach using Canva for teachers at Penggok 3 State Elementary School in Sragen yielded positive outcomes. Over 50% of teachers successfully created LKPD and educational videos using the CRT approach through Canva. Additionally, there was a 14.3% increase in understanding of the CRT approach, based on pre-test and post-test results.